Decolonizing Beginning Literacy Instruction: Views From Ugandan Teachers. (4th October 2020) - Beach, Sara Ann (Sally); Nyirumbe, Sr. Rosemary; Monk, David; Pia Okecha, Sr. Esther
Abstract: The International Literacy Association is a global advocacy organization, and literacy is viewed as a human right worldwide. This department highlights research and research‐to‐practice at the international level to bring global best teaching practices to the forefront. Topics may include best practices for literacy instruction in Europe or other continents/countries, partnership and collaborative projects between international schools/teachers, and advocacy.